Performance analysis of nano-refrigerants used in the vapor compression refrigeration system using MATLAB-Simulink. (June 2022) - Katoch, Anirudh; Razak, Fadil Abdul; Suresh, Arjun; BS, Bibin; Gundabattini, Edison
This paper investigates the performance of four nano-refrigerants (CuO-R113a, Al2 O3 -R134a, ZnO-R152a, and TiO2 -R600a) in terms of coefficient of performance and compressor power consumption using a MATLAB-Simulink two-phase flow domain vapor compression refrigeration cycle. The analyses are done for volume concentrations of 0.1%, 0.3%, and 0.5% of nanoparticles in the base-refrigerants. The results are derived mathematically in the Simulink model. The thermophysical properties of base-refrigerants were derived using the NIST chemistry webbook, and various mathematical models were applied to base-refrigerants to calculate the properties of nano-refrigerants. The interpolation of the liquid–vapor region was done using MS Excel. It was found that nano-refrigerants have better heat transfer characteristics and showed the best performance at a lower optimum concentration of 0.1%. Nano-refrigerant combinations have been tested in real-time and model validations; inferences have been duly reported.